Cathepsin D activity in cases of uterine leiomyoma - Dariusz Szajda, Sławomir; Zalewska, Beata; Michalak, Kamil; Skrzydlewski, Zdzisław (Contemporary Oncology/Współczesna Onkologia, 2004)
Cathepsin D is one of proteolitic cascade enzymes involved in the process of cancer development. Physiological wearing out and decomposition of cells of various tissues and organs as well as elimination of residual corpuscles out of cells by way of exocytosis results in the occurrence of trace quantities of this enzyme in the serum and body fluids. Significant intensification of the damage and increase in cathepsin D activity in the blood takes place in certain pathological conditions. Therefore, the determination of cathepsin D activity in the serum may have a diagnostic value. The goal of the study has been to determine cathepsin D activity in uterine leiomyoma homogenates as well as in control tissues and in the serum of uterine leiomyoma patients and healthy controls. In the present study cathepsin D activity in homogenates of uterine leiomyomas and healthy muscle tissue of the uterus as well as in serum of women with uterine leiomyoma and healthy ones has been estimated in 18 cases. The activity of the examined enzyme was determined in 10% homogenates of uterine leiomyomas and of healthy tissue of the uterus muscle as well as in the serum using the Folin-Ciocalteau method in the cupric modification and this activity was expressed as a quantity of released tyrosine in nM Tyr/ml/2h. Cathepsin D activity was estimated to be 151.5±36.2 nM Tyr/ml/2h and 80.8±17.8 nM Tyr/ml/2h in homogenates of uterine leiomyomas and unchanged tissues, respectively. Similarly, cathepsin D activity in serum of women with uterine leiomyoma is 40.5±13.5 nM Tyr/ml/2h whereas that of healthy women was 26.5±11.8 nM Tyr/ml/2h. Values obtained from examined and control material were significantly different in statistic terms (p<0.001). Our study suggests that the determination of cathepsin D activity may be useful in gynecological oncological diagnostics as complementary information in relation to histopathological examination.